ChemInform Abstract: Cu3V2O8 Nanoparticles as Intercalation‐Type Anode Material for Lithium‐Ion Batteries. Issue 43 (7th October 2016) - Li, Malin; Gao, Yu; Chen, Nan; Meng, Xing; Wang, Chunzhong; Zhang, Yaoqing; Zhang, Dong; Wei, Yingjin; Du, Fei; Chen, Gang
Abstract: Cu3 V2 O8 nanoparticles (40‐50 nm) are prepared by addition of NH4 VO3 to an aqueous 0.1 M Cu(NO3 )2 solution followed by drying and sintering of the Cu3 V2 O7 (OH)2 ·2H2 O precipitate in air (400 °C, 1 h).